Pengaruh Model Pembelajaran Inkuiri Terbimbing Berbantuan Artificial Intelligence terhadap Kemampuan Berpikir Ilmiah Peserta Didik SMPN 8 Gresik pada Pembelajaran IPS - Pirana Rachma Sari; Agus Suprijono; Nuansa Bayu Segara (Universitas Hamzanwadi, 2026)
Education is an important and useful thing in improving the standard of human life; through education, participants can improve skills that lead to a changing learning process. Education in the 21st century requires a transformation of learning that fosters deeper engagement with knowledge and encourages adaptive problem-solving. One of the skills that needs to be developed in Social Studies learning is scientific thinking ability. The inquiry-based learning model is one of the student-centered learning models that sharpens thinking skills through exploration and problem-solving. Artificial intelligence is a technology that helps students in learning, so that students can easily obtain information. This study aims to analyze the effect of the Artificial Intelligence (AI)-assisted guided inquiry learning model on the scientific thinking skills of eighth-grade students at Junior High School 8 Gresik. This research uses a quantitative approach with a non-equivalent control group experimental design. Data was collected through pretests and posttests, as well as observation sheets, and then analyzed using statistical tests. The research results indicate that the application of the Artificial Intelligence-assisted guided inquiry learning model significantly impacts the improvement of students' scientific thinking abilities. This model is effective in promoting scientific inquiry, analysis, inference, and argumentation activities in social studies learning.